(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
In this study ,the adsorption of an industrial blue dye was investigated by usingpomegranate peel in different size . The effect of the process parameters such as , contact time; adsorbate concentration pH) and (temperature ) are reported . "Nearly 2-3 hr of contact timeare found to be sufficient for the adsorption to reach equilibrium" (Abetter fixation wasobtained at acidic pH (2) and room temperature 25?C.